2003
DOI: 10.1093/ageing/32.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Ageism in the management of lung cancer

Abstract: this national study of lung cancer care in the UK has shown large age-related differences in management and survival in patients with lung cancer, largely independent of case-mix factors. The reasons for this are complex but such under-treatment in the elderly may be one factor underlying the poor outcomes in lung cancer patients in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(88 citation statements)
references
References 26 publications
6
80
0
2
Order By: Relevance
“…Our results on investigations and referral agree with other reports that have found that patients are less likely to be investigated or treated for cancer if they are elderly (e.g., Turner et al, 1999;Peake et al, 2003;Bouchardy et al, 2007). However, most other studies are hospital based and do not investigate what happens in primary care.…”
Section: Discussionsupporting
confidence: 90%
“…Our results on investigations and referral agree with other reports that have found that patients are less likely to be investigated or treated for cancer if they are elderly (e.g., Turner et al, 1999;Peake et al, 2003;Bouchardy et al, 2007). However, most other studies are hospital based and do not investigate what happens in primary care.…”
Section: Discussionsupporting
confidence: 90%
“…22,23 Although the prognosis of untreated patients is poor, 19 the mortality and morbidity of surgery, combined with the poor results from conventional radiotherapy, led to the widespread perception among patients and physicians that advanced age combined with the presence of comorbidities is a reason to defer from curative treatment. 24,25 Recent publications have reported local control rates for SRT that are in the range reported with surgery; and, notably for a patient cohort with considerable comorbidities, SRT is associated with a low incidence of grade !3 toxicity (Table 3). 5,26,27 Our results in 193 patients aged !75 years indicate that SRT is well tolerated even in patients with significant comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Our study undermines this practice and supports standard definitive treatment for the elderly with good performance status. Predicted risk of Grade ≥3 Esophagitis at seven different D2cc doses as a function of age for a hypothetical patient who is assumed to be a never smoker with a KPS of 85, who is receiving concurrent chemotherapy.…”
Section: Discussionmentioning
confidence: 64%